The Garden of Stars (Benjamin New Co., Ltd.)
The Garden of Stars - a unique triangular building in the heart of La Ronde features Children's Theatre in the morning and early afternoon, "Action Time" for the younger jet-set in the late afternoon and Musical Revues in the evenings.